ULTRASONOGRAPHIC MEASUREMENTS OF BULBO URETHRAL GLANDS IN DEVELOPING MURRAH BUFFALO - RANGA, L C; CHANDOLIA, R K; PHULIA, S K; SINGH, LAXMAN (The Indian Journal of Animal Reproduction, 2023)
The study was undertaken in buffalo-bull calves to study developmental dimensions of the bu Ibo-urethralgland (BUG) from 1 to 30 months of age with ultrasound scanning of the gland. The mean circumference of theBUG in the present study from 1st to 30th month increased significantly @ 0.37 cm per month. The increase inmean circumference of BUG exhibited a pattern parallel to increase in body weight. The mean length of BUGincreased significantly @ 0.16 cm per month during the study period. The correlation co-efficient of length ofBUG with age was r2 = 0.75 and with body weight was r2=0.76. The mean width of BUG from 1st to 30th monthranged between 1.02 ± 0.06 to 3.15 ± 0.11 cm. It increased @ 0.07 cm per month. The correlation co-efficientbetween age and BUG width was r2=0.68 and between body weight and BUG was r2=0.70.
Keywords: Buffalo; bull calves; Bulbourethral; Prepubertal; Development